Implementing Digital Marketing To Enhance The Effectiveness Of Automotive Service MSMEs Shine Pro Auto Protection - Fadhil Farizi Mursyidan; Mahrinasari MS (MINOVa Ditria Jaya, 2025)
Shine Pro Auto Detailing is an MSME operating in the automotive maintenance services sector, specifically interior-exterior detailing and ceramic coating. Established in 2022 in Bandar Lampung, Shine Pro has gained public attention through digital marketing based on video content and premium service positioning. However, the business faced challenges in creating consistent marketing strategies and building customer loyalty.This community service activity aimed to provide direct assistance to Shine Pro through digital marketing training, development of a membership service system, and social media optimization strategies to strengthen its positioning as a pioneer in content-based professional detailing in Lampung. The methods used include observation, interviews, documentation, benchmarking, and practical implementation. The results indicate a significant increase in content quality, customer service systems, and social media engagement. Total Instagram views reached 310,655, with 138,508 accounts reached—up from only 50,249 views and 22,938 accounts previously. This confirms the substantial impact of contextual, structured digital marketing approaches on improving MSME promotional effectiveness